Synthese des resultats obtenus entre octobre 1981 et avril 1984 et indications concernant les futures activites de recherche - Cisse, M.I. (International Livestock Centre for Africa, 1984)
Briefly outlines the ILCA semi arid zones programme's history and research achievements in livestock production systems, pasture ecology, animal health, animal nutrition and plant ecology in Mali; indicates future research programmes.